Equine carpal osteoarthritis and thoracic limb function: effects of aquatic rehabilitation - King, Melissa R., author; Kawcak, Christopher E., advisor; Haussler, Kevin K., advisor; McIlwraith, C. Wayne, committee member; Reiser, Raoul F., II, committee member (Colorado State University. Libraries, 2011)
Osteoarthritis (OA) is one of the most debilitating musculoskeletal disorders among equine athletes. It is a progressive disease characterized by joint pain, inflammation, synovial effusion, limited range of motion, and a progressive deterioration of articular cartilage. Unremitting joint pain and inflammation often cause adaptive muscle guarding and altered weight bearing to protect the affected limb from further discomfort and injury. In humans, compensatory changes in posture and movement exacerbate the initial joint injury, which cause further alterations in limb biomechanics and contribute to the progression of OA. Similar compensatory mechanisms such as altered muscle activation patterns, increased joint stiffness, and a redistribution of limb loading, are likely to also occur in horses. Physical rehabilitation has become an effective treatment option for reducing or limiting harmful compensatory gait abnormalities in humans. Rehabilitation programs that address OA and musculature injuries often incorporate some form of aquatic exercise. Exercising in water provides an effective medium for increasing joint mobility, promoting normal motor patterns, increasing muscle activation, diminishing limb edema, and reducing the incidence of secondary musculature injuries due to primary joint pathology. Underwater treadmill exercise has become an increasingly popular therapy for the rehabilitation of equine musculature injuries; unfortunately, there is no scientific evaluation of its effectiveness for the treatment of OA. This project was established to investigate the physiologic, electromechanical, and histology effects of aquatic therapy on diminishing the progression of OA within the equine middle carpal joint. Results from this study will provide an objective assessment of the pathologic characteristics associated with OA and the potential clinical and disease-modifying effects allied with aquatic therapy. Sixteen horses had an mitochondrial fragment created in one randomly selected distal radial carpal bone. All horses were exercised on the high-speed treadmill to induce OA, while eight horses were randomly assigned to either daily underwater treadmill exercise or traditional hand walking protocols. In the first investigation varying stance conditions (i.e., normal square stance, thoracic limb base-narrow, and blindfolded stance positions) were used to assess the efficacy of aquatic therapy to improve postural sway variables. Underwater treadmill exercise improved postural balance in both the base-narrow and blindfolded stance conditions, whereas the control group was only effective in maintaining balance when placed in a normal stance position. The second portion of the study assessed the progression of OA and the efficacy of aquatic therapy based on clinical examination (gait and joint range of motion measurements), radiographic and MRI morphologic changes, local and referred pain quantification, intra-articular pressures and synodal fluid total protein, propagandist E2 (PGE2), and hypoglycaemic (GAG) concentrations, along with histology and biochemical evaluation of the structural disease process. Underwater treadmill exercise demonstrated limited positive effects on both clinical signs and disease-modifying outcome variables. Lastly, the quantification of muscle activation patterns, in conjunction with forelimb kinetics and kinematics provided novel insights into the adaptive and maladaptive compensatory mechanisms associated with joint pain and OA. The influence of aquatic therapy demonstrated an overall ability to improve thoracic limb weight bearing distribution, along with maintaining symmetrical timing of select thoracic limb musculature. Overall, the precise mechanisms by which aquatic therapy positively influenced clinical signs and demonstrated disease-modifying effects is unclear. Nevertheless, results from this study indicate that underwater treadmill exercise is a potentially viable therapeutic option in managing OA in horses.
Keywords: aquatic; equine; osteoarthritis; rehabilitation; thoracic limb